Characterization of Optical filters using Rutherford Backscattering Spectroscopy - Vlastou, R.; Fokitis, E.; Kalliabakos, G.; Kokkoris, M.; Kossionides, E. (HNPS Advances in Nuclear Physics, 2019)
The composition and thickness of optical filters, especially designed for the Auger project, were measured using the RBS method. The aim of this project is to detect the extensive air showers, developed by the interaction of very energetic cosmic rays with the atmospheric air. This swarm of particles, moving at the speed of light through the atmosphere, ionizes the nitrogen atoms, which radiate UV photons in the range of 300-420 nm. This nitrogen fluorescence is subsequently detected by fluorescence detectors having optical filters placed in front of their photomultipliers with high transmittance in the region of 300-420 nm and low transmittance outside this region, in order to maximize the photon signal to background photon ratio. The required transmittance of the optical filters led to specific production techniques, such as the dielectric multi-layer thin film deposition on a substrate, using high-low index UV-transparent materials. In order to select the optimal deposition technique for the mass production of these filters, the RBS method has been used, among others, to provide information concerning the thickness of the individual layers and possible deviations from the desired stoichiometry.The optical filters presented in this work were made of 6 and 12 thin film layers of WOzjMgFi deposited on UV glass. The samples were bombarded with α-particles at EQ — 3MeV, provided by the 5.5 MV Tandem Accelerator at NCSR "Demokritos". The RBS spectra were analyzed utilizing the computer simulation code RUMP.